2014
DOI: 10.33899/rden.2014.160888
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nickel Ion Release from Orthodontic Wires in Different Types of Artificial Saliva

Abstract: ‫اﻟﺨﻼﺻﺔ‬ ‫اﻷﻫﺪاف‬ : ‫ات‬ ‫ﻓﱰ‬ ‫ﰲ‬ ‫و‬ ‫ﳐﺘﻠﻔﺔ‬ ‫اﺻﻄﻨﺎﻋﻴﺔ‬ ‫ﻟﻌﺎب‬ ‫ﰲ‬ ‫اﻷﺳﻨﺎن‬ ‫ﺗﻘﻮﱘ‬ ‫ﻟﻘﻮس‬ ‫ﻟﻠﺼﺪأ‬ ‫اﳌﻘﺎوم‬ ‫اﻟﻔﻮﻻذ‬ ‫اﺳﻼك‬ ‫ﻣﻦ‬ ‫اﺣﺔ‬ ‫اﳌﺰ‬ ‫اﻟﻨﻴﻜﻞ‬ ‫أﻳﻮﻧﺎت‬ ‫ﻛﻤﻴﺔ‬ ‫ﻗﻴﺎس‬ ‫إﱃ‬ ‫اﺳﺔ‬ ‫اﻟﺪر‬ ‫ﻫﺬﻩ‬ ‫ﺗﺪف‬ ‫ﳐﺘﻠﻔﺔ.‬ ‫زﻣﻨﻴﺔ‬ ‫اﻟﻌﻤﻞ‬ ‫اﺋﻖ‬ ‫وﻃﺮ‬ ‫اﻟﻤﻮاد‬ ‫ﻏﲑ‬ ‫اﳌﺎء‬ ‫ﳏﻠﻮل‬ ‫ﰲ‬ ‫ﻏﻤﺮﻫﺎ‬ ‫ﰎ‬ ‫ﳐﺘﻠﻔﺔ‬ ‫ﺑﺄﻗﻄﺎر‬ ‫اﻟﺘﻘﻮﳝﻴﺔ‬ ‫ﻟﻠﺼﺪأ‬ ‫اﳌﻘﺎوم‬ ‫اﻟﻔﻮﻻذ‬ ‫ﻷﺳﻼك‬ ‫ﳐﺘﻠﻔﺔ‬ ‫ﻳﺔ‬ ‫ﲡﺎر‬ ‫اع‬ ‫اﻧﻮ‬ ‫ﺳﺖ‬ ‫اﺳﺔ‬ ‫اﻟﺪر‬ ‫ﻫﺬﻩ‬ ‫ﴰﻠﺖ‬ : ) ‫اوﺣﺖ‬ ‫ﺗﺮ‬ ‫اﻟﻐﻤﺮ‬ ‫ات‬ ‫وﻓﱰ‬ ‫ﳐﺘﻠﻒ‬ ‫اﺻﻄﻨﺎﻋﻲ‬ ‫ﻟﻌﺎب‬ ‫اع‬ ‫اﻧﻮ‬ ‫ﺛﻼث‬ ‫و‬ ‫اﳌﺘﺄﻳﻦ‬ 7 ، 14 ‫و‬ 30 )) ‫اﻟﺬ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The present research established that the NiTi-2 alloy, which has a more stable microstructure with smaller grains and a higher grain number, is more biologically resistant. It also showed that Ni ion release was not proportional to the content of nickel in the alloy samples, a finding that is in accordance with previous investigations [ 34 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present research established that the NiTi-2 alloy, which has a more stable microstructure with smaller grains and a higher grain number, is more biologically resistant. It also showed that Ni ion release was not proportional to the content of nickel in the alloy samples, a finding that is in accordance with previous investigations [ 34 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, various studies have demonstrated lower corrosion resistance of these alloys in acidic solutions and chloride-containing environments [ 31 , 33 , 34 ]. In general, it is well documented that the corrosion potential increases as the pH value decreases [ 33 , 34 , 35 ]. The acidic environment had a significant effect on increasing the release of toxic ions from both groups of samples.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different parts of the human body vary significantly in oxygen concentrations and pH values. Various studies have demonstrated lower corrosion resistance of these alloys in acidic solutions and chloride-containing environments [14][15][16]. In general, it is well documented that the corrosion potential increases as the pH value decreases [17].…”
Section: Corrosion Resistancementioning
confidence: 99%
“…In turn, these elements may cause allergic reactions and potential cytotoxic effects that may jeopardize the health of patients. [23][24][25] Thus, extra information regarding the effect of APF gel on the surface characteristics of orthodontic wires is important. Furthermore, advance imaging techniques such as Energy Dispersive X-Ray Spectroscopy (EDX) which is the most standard and consistent method in the field of analytical electron microscopy can provide more detailed information about the effect of APF gel on orthodontic wires.…”
Section: Introductionmentioning
confidence: 99%